Effects of Working Memory Load on Visual Selective Attention: Behavioral and Electrophysiological Evidence - Pratt, Nikki; Willoughby, Adrian; Swick, Diane (Frontiers in Human Neuroscience, 2011)
Working memory and attention interact in a way that enables us to focus on relevant items and maintain current goals. The influence of working memory on attention has been noted in several studies using dual task designs. Multitasking increases the demands on working memory and reduces the amount of resources available for cognitive control functions such as resolving stimulus conflict. However, few studies have investigated the temporal activation of the cortex while multitasking. The present study addresses the extent to which working memory load influences early (P1) and late (P300) attention-sensitive event-related potential (ERP) components using a dual task paradigm. Participants performed an arrow flanker task alone (single task condition) or concurrently with a Sternberg memory task (dual task condition). In the flanker task, participants responded to the direction of a central arrow surrounded by congruent or incongruent arrows. In the dual task condition, participants were presented with a Sternberg task that consisted of either 4 or 7 consonants to remember prior to a short block of flanker trials. Participants were slower and less accurate on incongruent versus congruent trials. Furthermore, accuracy on incongruent trials was reduced in both dual task conditions. Likewise, P300 amplitude to incongruent flanker stimuli decreased when working memory load increased. These findings suggest that interference from incongruent flankers was more difficult to suppress when working memory was taxed. In addition, P1 amplitude was diminished on all flanker trials in the dual task condition. This result indicates that top-down attentional control over early visual processing is diminished by increasing demands on working memory. Both the behavioral and electrophysiological results suggest that working memory is critical in maintaining attentional focus and resolving conflict.